Clinical Presentation and Risk Factors for Poor Outcomes Among Adult Patients With Posterior Reversible Encephalopathy Syndrome: A Retrospective Cohort Study. Issue 6 (November 2020) - Vallone, Marcelo G.; Vázquez, Carolina; Pigretti, Santiago; Oses, Lucrecia L.; Angriman, Federico; Zurru, María C.
Abstract : Background: Posterior reversible encephalopathy syndrome (PRES) is an acute neurological condition with unknown global incidence, variable clinical presentation, and prognosis. Objectives: To describe a cohort of patients with PRES with a focus on brain magnetic resonance imaging (MRI) patterns and their relationship with short-term clinical outcomes. Methods: Retrospective cohort study. The authors included patients if they were older than 15 years and had a PRES diagnosis on the basis of a positive brain MRI at any time during the in-hospital stay. Results: Forty-four patients were included in the present analysis. The median age was 57 years (interquartile range, 32.0-68.5) and 70.5% were women. Hypertension (59.1%), history of transplantation (27.3%), previous chemotherapy (27.3%), chronic renal failure (38.6%), and autoimmune disease (15%) were the main comorbid conditions present. The classic triad of seizures, headache, and visual impairment was present in 18.0% of the cases. Eighty-six percent of patients were admitted to the intensive care unit, with 36.0% needing invasive life support. Brain MRI showed a dominant parieto-occipital pattern in 26 patients, whereas cytotoxic edema and bleeding were present in 27.3% and 29.6%, respectively. In-hospital mortality was 11.4%. The median modified Rankin Scale at hospital discharge was 1 (0-2.5). Risk factors associated with low modified Rankin Scale scores were: headache, visual impairment, and parieto-occipital pattern. Decreased level of consciousness and mechanical ventilation requirement were associated with greater discharge disability. Conclusions: Characteristic symptoms and signs of PRES and classic MRI patterns are associated with better clinical outcomes. Abstract : Supplemental Digital Content is available in the text.